KOMPARASI KONSEP BELAJAR IBNU KHALDUN DENGAN PROGRESSIVISME - Siswadi Siswadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : Ibn Khaldun as a whole person, knowledgeable with a variety of expertise, this is mainly manifested in the brilliant thoughts thatgave birth to the concepts, theories and fatwas become the next generation of role models, including the concepts of education and learning concepts. Furthermore, from multiple streams of education writers take progressivisme as a comparison, because progressivisme regarded as a representative flow. Therefore, the authors restrict this paper to learn the concept of comparative analysis of Ibn Khaldun’s philosophy of education with the West, with the announced one of the streams in the progressivisme philosophy in order to find alternative methods of proper Islamic education. Key Words: Comparison, Learnig, Ibn Khaldun, and Progressivisme.